Bentuk arsitektur Kedai Kopi di Bentuk Arsitektur Kedai Kopi di Bagan Siapiapi Kabupaten Rokan Hilir - Jumino, Yusril Hanafi; Repi; Samra, Boby (Jurusan Arsitektur UPR, 2025)
Coffee shops in Bagansiapiapi , Rokan Hilir Regency, constitute an important form of everyday architecture that contributes to the social and cultural identity of the local community. Beyond their function as culinary facilities, coffee shops serve as social spaces that reflect the historical interaction between Malay and Chinese cultures since the city’s development in the late nineteenth century. This study aims to examine the architectural typology of coffee shops in Bagansiapiapi by analyzing building forms, spatial configurations, and their social functions within the local historical and cultural context. The research employs a qualitative descriptive method through literature review, field observation, and architectural analysis based on local context. The typological analysis is conducted by identifying recurring patterns and variations in form and spatial organization found in coffee shops operated by the Malay community and those located in the Chinatown area. The findings reveal that the architectural typology of coffee shops in Bagansiapiapi has developed as a hybrid form that integrates elements of Malay and Chinese vernacular architecture. This typology is characterized by the use of terraces as commercial spaces, the integration of residential and business functions, open front façades, and spatial arrangements influenced by cultural philosophies such as the separation of water and fire elements derived from Feng Shui and Taoist thought. Furthermore, coffee shops function as third places that facilitate cross-ethnic social interaction and form part of the daily rhythm of community life. This study highlights that the architectural typology of coffee shops in Bagansiapiapi possesses not only functional value but also significant historical, social, and cultural significance, underscoring the importance of its preservation as part of the local architectural identity.